Sleep apnea and autonomic dysfunction in patients with dementia - Herberts, Michelle; Kolla, Bhanuprakash; Paul, Travis; Mekala, Praveen; Mansukhani, Meghna P. (Frontiers in Neuroscience, 2022)
Sleep apnea is common sleep disorder that is associated with an is an increase in risk of many 24 health conditions, including systemic hypertension, stroke, atrial fibrillation, and heart failure. 25 The predominant underlying pathophysiological mechanism for elevated risk of these 26 conditions in patients with sleep apnea is thought to involve autonomic dysfunction in the form 27 of sympathetic overactivity. Autonomic dysfunction is also associated with several 28 neurodegenerative disorders and sleep apnea, in turn, has been shown to be associated with an 29 increased risk of development of mild cognitive impairment and various types of dementia. 30 Rapid eye movement sleep behavior disorder, which is also associated with an increased risk of 31 alpha synucleiopathy-related dementia, is also linked with autonomic dysfunction. In this 32 article we explore the relationship between sleep apnea, autonomic dysfunction, rapid eye 33 movement sleep behavior disorder and dementia. This article describes the various autonomic 34 dysfunction that are thought to occur in the context of sleep apnea. And illustrate the 35 mechanisms by which sleep apnea, through its impact on autonomic dysfunction could